POTENTIAL ANTIDIABETIC OF TAMARIND WASTE: EFFECTS ON THE PANCREATIC -AMYLASE - Driele Cardoso Bueno; Gustavo Henrique de Souza; Beatriz Paes Silva; Rosane Marina Peralta; Lívia Bracht; Jurandir Fernando Comar; Adelar Bracht; Anacharis Babeto de Sá-Nakanishi (Arquivos do Mudi, 2023)
Diabetes is a complex metabolic disease characterized by plasma hyperglycemia. One of theways of treatment of diabetes is the inhibition of pancreatic α-amylase. However, drugsavailable in the market carry out a range of side effects. Therefore, the present work aimed toevaluate the effect of tamarind waste (skin and seed) rejected by the food industry on theactivity of pancreatic α-amylase. Hydroethanolic extract (70%) of tamarind skin and seedwere prepared, lyophilized, and used in a concentration curve on the α-amylase activity by 3,5dinitro-salicylate assay. Kinetic analysis was performed simultaneously varying both substrate(starch) and extracts. Statistical analyses were carried out by Scientist Program. Both extracts(skin and seed) reduced the enzymatic activity in a concentration dependence way. However,the seed extract reported a bigger strength of inhibition, as revealed by IC 50 of 13,26 µg/mL,compared to IC 50 of 470,16 µg/mL for skin extract. Kinect studies showed that the seedextract presented an enzymatic inhibition of parabolic and non-competitive type (KI 1 10,07µg/mL e KI 2 10,37 µg/mL). Conversely, skin extract performed a mixed linear inhibition (KI 1615,78 µg/mL e KI 2 411,01 µg/mL). We concluded that tamarind waste, mainly seed extract,can be considered preparation with therapeutic potential for the management and treatment ofdiabetes.